COMPARATION OF WAREHOUSE RECEIPT, PAWN AND FIDUCIARY IN THE SECURITY LAW PERSPECTIVE - Iswi Hariyani (Faculty of Law, Universitas Sebelas Maret, 2017)
Warehouse Receipt System (WRS) has been used in Indonesia as an instruments of trade and finance to agribusiness commodities since the enactment of Law UU 9/2006 and PBI 9/2007. Bank Indonesia Regulation No 9 of 2007, Article 46 letter f, allows the use of Warehouse Receipt as a credit collateral. Implementation of Warehouse Receipt System is expected to help farmers, planters, fishermen who have often had difficulty costs at harvest time. As securities, Warehouse Receipt can also be used as an investment instrument in the commodity market. This research aims to find answers of three main problem. First, to examine legal position of Warehouse Receipt in Security Law perspective. Second, to examine differences and similarities of Warehouse Receipt collateral to the Pawn guarantees. Third, to examine differences and similarities between Warehouse Receipt collateral with Fiduciary guarantees. Key word : security law, warehouse receipt, pawn, fiduciary